Pengaruh Leverage, Kepemilikan Manajerial, dan Kompensasi Bonus terhadap Income Smoothing pada Perusahaan Sektor Consumer Non-Cyclicals di Indonesia (2020-2024) - Januar Eko Prasetio; Anggita Maysa Amaliasari (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to analyze the effects of leverage, managerial ownership, and bonus plan on income smoothing in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange during the 2020-2024 period. The research population consists of 85 companies, and through the use of a purposive sampling technique, 70 companies were selected, resulting in a total of 350 samples. The study employs binary logistic regression, with income smoothing measured using the eckel index, leverage measured by the debt to-asset ratio, managerial ownership measured by the proportion of shares held by management, and bonus plan proxied by the natural logarithm of salary expenses. The results indicate that leverage does not affect income smoothing, while managerial ownership and bonus plan have a significant effect on income smoothing. These findings suggest that in a relatively stable sector, income smoothing practices are more strongly driven by internal governance mechanisms and managerial incentive structures, as explained by agency theory, than by external financial pressure related to debt covenants. This study contributes to the income smoothing literature by highlighting the dominant role of internal factors over external financing constraints in shaping managerial reporting behavior.